Short Report: Consensus Guidelines for Dosing of Amoxicillin-Clavulanate in Melioidosis - Cheng, Allen C. (2008)
Melioidosis is an infectious disease endemic to northern Australia and Southeast Asia. In response to clinical confusion regarding the appropriate dose of amoxicillin-clavulanate, we have developed guidelines for the appropriate dosing of this second-line agent. For eradication therapy for melioidosis, we recommend 20/5 mg/kg orally, three times daily.